2012
DOI: 10.2174/156802612799984544
|View full text |Cite
|
Sign up to set email alerts
|

Derivatives of 3-Isoxazolecarboxylic Acid Esters - A Potent and Selective Compound Class against Replicating and Nonreplicating Mycobacterium tuberculosis

Abstract: New antituberculosis (anti-TB) drugs are urgently needed to battle drug-resistant Mycobacterium tuberculosis (Mtb) strains and to shorten the long treatment regimen. A series of isoxazole-based compounds, bearing a carboxy moiety at the C3 position, are highly potent and versatile anti-TB agents. Several members of this compound class exhibit submicromolar in vitro activity against replicating Mtb (R-TB) and thus comparable activity to the current first-line anti-TB drugs. Remarkably, certain compounds also sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 16 publications
3
17
0
Order By: Relevance
“…This notion may sound odd, especially if one considers the first-line antituberculosis drugs: isoniazid and pyrazinamide both have negative ClogP, whereas ClogP of ethambutol is 0.35. However, it has been deeply demonstrated that compounds with antituberculosis activity are more lipophilic than the inactive ones (Ekins et al, 2011 ), and not only in general, but also within a drug class, lipophilic derivatives are in general more active against mycobacteria than their more hydrophilic counterparts (Mao et al, 2009 ; Lilienkampf et al, 2010 , 2012 ; Pieroni et al, 2010 , 2011 , 2017 ). Below, a critical analysis of the current hot biology challenges (energy depletion, PMF, and drug transporters) and their interconnection with the lipophilicity of molecules is reported.…”
Section: State-of-the-art Of Tuberculosis Drug Discoverymentioning
confidence: 99%
“…This notion may sound odd, especially if one considers the first-line antituberculosis drugs: isoniazid and pyrazinamide both have negative ClogP, whereas ClogP of ethambutol is 0.35. However, it has been deeply demonstrated that compounds with antituberculosis activity are more lipophilic than the inactive ones (Ekins et al, 2011 ), and not only in general, but also within a drug class, lipophilic derivatives are in general more active against mycobacteria than their more hydrophilic counterparts (Mao et al, 2009 ; Lilienkampf et al, 2010 , 2012 ; Pieroni et al, 2010 , 2011 , 2017 ). Below, a critical analysis of the current hot biology challenges (energy depletion, PMF, and drug transporters) and their interconnection with the lipophilicity of molecules is reported.…”
Section: State-of-the-art Of Tuberculosis Drug Discoverymentioning
confidence: 99%
“…This method has been adapted for direct utility with M. tuberculosis and has led to the identification of a number of promising lead compounds 4 . A recent phenotypic screening of a library of 6,800 compounds identified several chemotypes with anti- M. tuberculosis activity 58 . We synthesized and preliminarily characterized one molecular class, indoleamides, which was active against both drug-susceptible and drug-resistant M. tuberculosis 9 .…”
Section: Introductionmentioning
confidence: 99%
“…8 Indeed, most of the efforts of some of the authors of this work has moved through this path. [9][10][11][12][13][14][15][16][17][18][19] While this approach has proved to be correct, it is nevertheless incomplete. It does not consider that, besides mutations, other mechanisms such as efflux play an important role in the development of resistance in M. tuberculosis.…”
mentioning
confidence: 99%